PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SPIKPU UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SMA - Andi Melina Hutabarat (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
Application of Cooperative Learning Model SPIKPU to Improve Reading Comprehension Ability for Senior High School Students. This study aimed to describe the improvement of students' reading comprehension by applying cooperative learning model SPIKPU techniques. This technique consists of six stages, which set the mood, read to understand, remember, find fault, connecting with the experience, and repeat. This type of research is a classroom action research. Data collection techniques by observation, interview, test the ability to read, data were analyzed descriptively qualitative and quantitative. The results showed an increase in reading comprehension class XI student of State Senior High School 1 Sunggal, both process and product. Assessment process is demonstrated by the activity of learning more enjoyable, active and enthusiastic, while the product assessment is indicated by an increase in the mean score of 58.89 pracicly increased to 70.15 in the first cycle and the second cycle increased to 83.68.